A Combined In Vitro (Caco-2 Cell) and In Vivo (Gallus gallus) Assessment Reveals the Iron Benefits of Consuming the Fast Cooking Manteca Yellow Bean (Phaseolus vulgaris L.) (P10-114-19). (13th June 2019) - Wiesinger, Jason; Glahn, Raymond; Cichy, Karen; Kolba, Nikolai; Hart, Jon; Tako, Elad
Abstract: Objectives: The common dry bean ( Phaseolus vulgaris L.) is a globally produced pulse crop and an important source of protein and micronutrients for millions of people across Latin America and Africa. In these regions, energy for cooking is expensive or scarce and long cooking times deter consumers from purchasing beans. In addition, many of the preferred black and red seed types have phytate and polyphenols that limit the absorption of trace minerals. Yellow beans are unique because their seed coats are rich in kaempferol 3-glucoside, a recently discovered promoter of iron absorption. Several market classes of yellow beans are sold throughout Latin America and Africa, where they are marketed at premium prices for their fast cooking tendencies. Exploring the yellow bean's unique heritage to develop new fast cooking varieties that deliver more absorbable iron would be useful for regions where inhabitants have limited access to fuelwood for cooking. This study compared the iron bioavailability of three fast cooking yellow beans from Africa with contrasting seed coat colors (Manteca, Amarillo, Njano) to slower cooking white and red kidney commercial varieties from North America (Table 1 ). Methods: Cooked beans were formulated into diets with the complementary food crops of potato, rice and cabbage. Iron bioavailability was measured as ferritin formation in an in vitro digestion Caco-2 bioassay and the ability to maintain total body iron hemoglobin (Hb-Fe) during a 6 week in vivo ( Gallus gallus ) feeding trial. Results: Animals fed yellow bean diets had faster growth rates, accumulated more dietary iron and had higher Hb-Fe than animals fed either kidney bean diet (Figure 1 ). In contrast to yellow beans, the kidney beans had almost no kaempferol 3-glucoside (Table 2 ). When compared to the other four bean based diets, the fast cooking Manteca yellow bean diet had the highest Caco-2 ferritin formation in vitro (Table 3 ) and delivered the largest increase in Hb-Fe in vivo (Figure 1 ). Conclusions: Through the added benefit of fast preparation times and improved iron quality after cooking, this study provides evidence that the Manteca market class is worthy of germplasm enhancement as a new convenience food to help alleviate trace mineral deficiencies in regions where beans are widely accepted as a dietary staple. Funding Sources: USDA-NIFA. Supporting Tables, Images and/or Graphs: